2020
DOI: 10.1016/j.cobeha.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

What can narratives tell us about the neural bases of human memory?

Abstract: Narratives are increasingly used to study naturalistic human memory and its brain mechanisms. Narratives-audiovisual movies, spoken stories, and written stories-consist of multiple interrelated and temporally unfolding events which are rich in semantic and emotional content. These characteristics drive intersubject neural synchrony in the default mode network, where abstract situation models are represented and reinstated. Medial temporal lobe structures interact with the cortical subregions of the default mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 70 publications
1
31
2
Order By: Relevance
“…Our results suggest that process memory may have two states: a state in which prior events are active and influence ongoing information processing and an inactive state in which the latent memory does not interfere with the ongoing neural dynamics (Hasson et al, 2015;Stokes, 2015). Through crossdisciplinary collaboration, this study demonstrated a way to achieve some experimental control over naturalistic stimuli, which play an ever-increasing role in revealing how the human brain works in its native environment (Lee, Bellana, & Chen, 2020;Willems, Nastase, & Milivojevic, 2020;Sonkusare, Breakspear, & Guo, 2019), and also showed how skilled storytellers leverage these mechanisms of separation and integration to bring about the desired effects in the listener's brain. Comparison between the within-participant RSA and between-participant RSA of the storyline effect.…”
Section: Discussionmentioning
confidence: 95%
“…Our results suggest that process memory may have two states: a state in which prior events are active and influence ongoing information processing and an inactive state in which the latent memory does not interfere with the ongoing neural dynamics (Hasson et al, 2015;Stokes, 2015). Through crossdisciplinary collaboration, this study demonstrated a way to achieve some experimental control over naturalistic stimuli, which play an ever-increasing role in revealing how the human brain works in its native environment (Lee, Bellana, & Chen, 2020;Willems, Nastase, & Milivojevic, 2020;Sonkusare, Breakspear, & Guo, 2019), and also showed how skilled storytellers leverage these mechanisms of separation and integration to bring about the desired effects in the listener's brain. Comparison between the within-participant RSA and between-participant RSA of the storyline effect.…”
Section: Discussionmentioning
confidence: 95%
“…If associative regions are still developing, infant event segmentation may be sensory-driven. However, ISC and event structure in infants was not limited to visual regions, extending into regions linked to narrative processing in adults (Lee et al, 2020). Furthermore, infants structured events over a longer timescale, consistent with their ability to represent more extended, complex content.…”
Section: Discussionmentioning
confidence: 99%
“…Despite potential difficulties in completely separating episodic and semantic retrieval effects, future experiments based on paradigms similar to that described here appear to hold great promise. One could, for example, scan participants both while they view (encode) and later recall film clips to better understand the specificity of the effects observed in the current report (for related discussion, see Lee et al 2020). Overt speech and verbal content scoring can also be applied to study cognitive phenomena beyond episodic memory.…”
Section: On the Separation Of Semantic And Episodic Memorymentioning
confidence: 99%